Cybersecurity And Personal Data Protection - Yuldasheva, Elmira; Ismoilova, Dilrabo (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article considers the current issues of cybersecurity and personal data protection. Along with the development of the Internet and digital technologies, the risks to personal data are increasing. The article analyzes the basic concepts of cybersecurity, modern threats, ways to identify and prevent them. It also discusses in detail legal and technical measures to protect personal data. Through practical recommendations, it is shown that organizations and individuals have the opportunity to effectively protect their data. The study aims to highlight existing problems in the field of cybersecurity and propose new approaches to effectively solving them.